LOYALITAS PELANGGAN PADA LION AIR YANG DIPENGARUHI OLEH EMOTIONAL BRANDING DAN BRAND TRUST - Muhammad Febrian; Hery Pudjoprastyono (Economos : Jurnal Ekonomi dan Bisnis, 2022)
Each company must have an effort to develop and increase sales to achieve the target. This study aims to determine the effect of emotional branding and brand trust on customer loyalty to Lion Air Airlines. Customers who have used this airline more than once will be involved in this research. Samples were taken from 65 respondents using the non-probability sampling method as a method for taking samples and purposive sampling techniques for taking samples. This study also uses the PLS (PartialLeastlSquare) technique as a research data analysis technique. In this study, primary data were obtained from questionnaires distributed to the respondents. The results obtained from this study emotional branding and brand trust have a positive effect on customer loyalty to Lion Air airline.